PROSPECTS FOR USING FLOW SUSPENSION CABLEWAY AT THE JERUY MINE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article considers the prospects for using a continuous overhead ropeway at the Jeruy mine for transporting ore to the ore stockpiles of the Gold Extraction Plant located below the quarry at elevation marks. The superiority of continuous overhead ropeways over automobile transport in mountainous terrain conditions is established. The expediency of using a continuous overhead ropeway in the development of the Jeruy gold ore deposit is revealed, which allows for a significant increase in economic indicators and an improvement in the environmental situation at the mine by abandoning automobile transport, as well as increasing safety during ore transportation. Comparative technical and economic calculations of the main indicators of automobile and continuous overhead rope transport for the conditions of the Jeruy mine are carried out.
Keywords: Jeruy, continuous, stations, overhead, rope, transport, support, trolley, mine, deposit, ore, automobile.